2000
DOI: 10.1063/1.371870
|View full text |Cite
|
Sign up to set email alerts
|

Photoemission study of aluminum/tris-(8-hydroxyquinoline) aluminum and aluminum/LiF/tris-(8-hydroxyquinoline) aluminum interfaces

Abstract: We have investigated the interfaces of aluminum on tris-(8-hydroxyquinoline) aluminum (Alq3) and aluminum on LiF/Alq3, using x-ray and ultraviolet photoemission spectroscopy (UPS). Aluminum appears to react destructively with Alq3 causing significant modification of the oxygen, nitrogen, and aluminum spectra. The well-defined UPS spectrum of Alq3 is quickly destroyed by very low coverages of aluminum. With only a 5 Å layer of LiF on the Alq3, the reaction with aluminum is significantly suppressed. The Alq3 mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(46 citation statements)
references
References 23 publications
1
45
0
Order By: Relevance
“…Experimentally, a lower binding energy state was observed for very thin (0.5-1 nm) Alq 3 on Ag [21] and Al [22]. The chemical reaction of Alq 3 with an Al electrode was reported [23], but on the Ag electrode, the lowering of the binding energy of the HOMO by about 0.5 eV was attributed to the formation of a polarized molecular layer, or interface dipole [21]. A reaction of Alq 3 with Au also seems unlikely.…”
Section: Resultsmentioning
confidence: 92%
“…Experimentally, a lower binding energy state was observed for very thin (0.5-1 nm) Alq 3 on Ag [21] and Al [22]. The chemical reaction of Alq 3 with an Al electrode was reported [23], but on the Ag electrode, the lowering of the binding energy of the HOMO by about 0.5 eV was attributed to the formation of a polarized molecular layer, or interface dipole [21]. A reaction of Alq 3 with Au also seems unlikely.…”
Section: Resultsmentioning
confidence: 92%
“…A detailed analysis has suggested that alkali halides undergo dissociation when Al is deposited on top, thus releasing the alkali-metal atom to react with the organic semiconductor in immediate proximity. [104][105][106][107][108] 2.1.6. Doped Charge-Transport Layers…”
Section: Low-work-function Cathodesmentioning
confidence: 99%
“…In this context, the use of alkali halides (e.g., LiF, CsF) has turned out to be very helpful in confining the organic/metal reacted region. A detailed analysis has suggested that alkali halides undergo dissociation when Al is deposited on top, thus releasing the alkali atom to react with the organic semiconductor in immediate proximity [47][48][49][50]. A particularly interesting low work function metal is Sm (φ ≈ 2.8 eV).…”
Section: Low Work Function Electrodesmentioning
confidence: 99%